Oralité écrite, littérale ou littéraire ? L’exemple des complaintes criminelles - Claude Ribouillault (Criminocorpus)
The wider context of what we call « to the tune of » repertory, including different laments about events (Natural disasters, wrecks and damas in transports as train, plane, even bicycle…) shows the specificity of criminal laments, more clearly « edifying », despite or within the high-flown and sometimes gauche use of the langage, the wish of employing a « good french », almost juridical, a particular rhetoric concerning the versification, the rhymes setting, the strategical telescoping between rhymes and melody (open/closed ; non conclusive even interrogative/conclusive)… These elements lock together, structuring links and differences, nearnesses and dissimilarities… The purpose, here, is to understand, through out the use of literary techniques, the work of the one who, betwixt the crime itself and the public, writes a song text wanting, pretty much skillfully, be moral and edifying.